Cytoskeletal tension actively sustains the migratory T‐cell synaptic contact - Kumari, S; Mak, M; Poh, Y-C; Tohme, M; Watson, N; Melo, M; Janssen, E; Dustin, M; Geha, R; Irvine, DJ (EMBO Press, 2020)
When migratory T cells encounter antigen‐presenting cells (APCs), they arrest and form radially symmetric, stable intercellular junctions termed immunological synapses which facilitate exchange of crucial biochemical information and are critical for T‐cell immunity. While the cellular processes underlying synapse formation have been well characterized, those that maintain the symmetry, and thereby the stability of the synapse, remain unknown. Here we identify an antigen‐triggered mechanism that actively promotes T‐cell synapse symmetry by generating cytoskeletal tension in the plane of the synapse through focal nucleation of actin via Wiskott–Aldrich syndrome protein (WASP), and contraction of the resultant actin filaments by myosin II. Following T‐cell activation, WASP is degraded, leading to cytoskeletal unraveling and tension decay, which result in synapse breaking. Thus, our study identifies and characterizes a mechanical program within otherwise highly motile T cells that sustains the symmetry and stability of the T cell–APC synaptic contact.